The World Cannot say anymore that Children are not the face of COVID-19 The Urgency to Detect, Respond to MICS, and Care for children in 2021 - Suresh Kishanrao (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Covid 19 pandemic has been showing disastrous effects across the world, since December 2019, affecting 220 countries, over 197 million cases and 4.2 million deaths by end July 2021, and huge economic loss, Political blame games and vaccine diplomacy and many social security measures. The pandemic also has exposed the limitation of Public Health capacities across the world. By now we know that Children of all ages can be affected. The fact that exact data of number of children affected or their proportion of the total infections or deaths, is not readily available even at subnational levels, indicates that they have not been the face of the Pandemic. In the initial months the symptoms and signs of the disease were very mild in children, until in May 2020, when a few cases of critical illness called Multisystem inflammatory syndrome in children were first reported in UK/USA.  Very few cases of mucor mycosis a fungal infection after recovering from Covid 19 are also being reported among children across the world. As of now available data indicates that children under the age of 18 years represent about 8.5% of reported cases and the symptomatic children are fewer and usually mild, and deaths were negligible compared to other age groups.   The complications of MICS and lack of vaccine are the two major hurdles in protecting the lives of the children as of now. The indirect impact is the Orphanhood due the death of millions of COVID-19-associated deaths of the parents, poverty due to diminished earning by the parents losing jobs or working for low wages, interruption in education due to closure of schools, increase in malnutrition in poor countries due to disruption of nutrition programs and mental health of the children for want of peer interactions and the tensions of online learning. After about one and half year analysis of the available data indicates that the Covid 19 Pandemic affects the world's children in three ways through: 1. infection with the virus and its complications like MICS and Mucor mycosis 2. the socioeconomic effects of the virus and related public health measures to suppress transmission and control the pandemic by the national and provincial Governments and 3. the risk that the virus and its response poses to the longer-term efforts to achieve the economic revival, efforts for Sustainable Development Goals (SDGs) and ensuring the realization of the rights of all children as committed by the national governments. Working with UNICEF India, for over 17 years, the author in this article tries to look at the data available and assess the impact of covid 19 pandemic on the children in short and long terms. Materials & methods: The author has reviewed the Covid 19 pandemic world dash boards, Periodical press and TV media reports, sub-national data of age and sex distribution of cases, small studies on the cases and deaths of Covid 19and it's complications and reports on the various development partners on the issue of child related SDGs.